Innovative power-to-gas plant concepts for upgrading of gasification bio-syngas through steam electrolysis and catalytic methanation. (1st March 2019) - Anghilante, Régis; Müller, Christian; Schmid, Max; Colomar, David; Ortloff, Felix; Spörl, Reinhold; Brisse, Annabelle; Graf, Frank
Highlights: Assessment of power-to-CH4 plants with Pinch technology & full thermal integration. Different biomass feedstocks, methanation & electrolysis technologies considered. Plant efficiency with SOE much higher than with low temperature electrolysis. Gasification allows a higher plant efficiency than anaerobic digestion. Residual heat valorization assessed for power production or district heating. Abstract: Several plant concepts for synthetic compressed natural gas (CNG) and liquefied natural gas (LNG) production using different water electrolysis and methanation technologies are compared in terms of power-to-methane efficiency, cooling water requirements, net water requirements, and carbon valorization. In these concepts, both oxygen and hydrogen produced in the electrolysis unit are valorized. Pure oxygen is used in the gasification unit, which allows a compact autothermal unit design and an efficient syngas production. Electrolytic hydrogen is fed to the catalytic methanation unit, thus improving the carbon utilization compared to state of the art plants with water-gas shift units. Pinch analyses were performed using an in-house MATLAB® algorithm to evaluate the thermal requirements of each plant concept and determine the maximal theoretical plant efficiencies. Plant efficiencies were then evaluated more accurately in static regime using full integrated Simulink® plant models. Calculated efficiency values are very close to the maximal theoretical ones, which validates the relevance of the implemented thermal integrations from an energy standpoint. Investigated plant concepts with solid oxide electrolysis (SOE) units present a significantly higher overall efficiency (in the range of 78.5–81.8% higher heating value (HHV) according to the end-products) compared to the reference case with liquid water electrolysis units (64.9% HHV for synthetic natural gas (SNG) or 64.4% HHV for CNG), thus highlighting the potential of the solid oxide electrolysis cell (SOEC) technology for power-to-gas/liquids applications. The plant efficiency values are then verified, discussed, and compared with previous literature values. The techno-economic feasibility of several options for residual heat valorization is then discussed, e.g. power production or coupling with a district heating network.